Ceramic oxide coating formed on beryllium by micro-arc oxidation. (1st July 2017) - He, Shixiong; Ma, Yanlong; Ye, Hong; Liu, Xiangdong; Dou, Zuoyong; Xu, Qingdong; Wang, Haijun; Zhang, Pengcheng
Highlights: Beryllium is oxidized in a Na2 CO3 electrolyte using DC micro-arc oxidation. The coating consists of an inner barrier layer and an outer porous layer. The coating shows improved corrosion resistance and insulation properties. XPS and XRD indicate that the coating is crystalline BeO. Abstract: Beryllium was oxidized at a current density of 10 mA cm −2 in a 0.5 M Na2 CO3 (pH = 11.2) electrolyte to understand the micro-arc oxidation (MAO) process. Different oxidation stages were investigated by analysing the voltage–time responses and coating morphology. 'Electric breakdown' accompanied by sparks travelling across the metal/electrolyte interface occurs when the voltage rises above a certain point (∼202 V), leading to the formation of an off-white 'ceramic-like' BeO coating. The MAO coating consists of two layers—an inner barrier layer and an outer porous layer—and shows improved corrosion resistance and insulation properties. XPS and XRD indicate that the coating has a chemical composition of BeO and is crystalline. Further, corrosion resistance and insulation properties of the coating were estimated by EIS analysis.